Habitação gerontológica: os desafios para moradias individuais - Pires, Thaisa Fraga (2015)
The growth of the elderly population in Brazil increases the demand for adequate housing in the civil construction industry. An environment adapted to the needs of the elderly ensures a better quality of life, promoting independence and safety of its users. From an interdisciplinary literature review covering accessibility, ageing, the legislation about the previous themes and the gerontological collective housing in Brazil, the objective of this work is to analyze the current situation of older persons and to propose the basic adequacies for individual housing. By looking at factors such as physical barriers, gaps, appropriate dimensions, lighting and ventilation, it is possible to create an ideal environment for living for senior citizens.